Reduced physical activity in lymphangioleiomyomatosis compared with COPD and healthy controls: disease-specific impact and clinical correlates. Issue 7 (11th March 2016) - Bahmer, Thomas; Watz, Henrik; Waschki, Benjamin; Gramm, Marco; Magnussen, Helgo; Rabe, Klaus F; Wirtz, Hubert; Kirsten, Detlef; Kirsten, Anne
Abstract : Rationale: Sporadic lymphangioleiomyomatosis (LAM) is an orphan lung disease for which daily physical activity has not been studied so far and it is unclear whether a disease-specific impact beyond airflow limitation exists. Clinical correlates indicating reduced physical activity in addition to established parameters like airflow limitation and hypoxaemia are largely undetermined. Method: We measured physical activity (steps per day, SPD; physical activity level, PAL; minutes of moderate activity, MMA) in 34 women with LAM, 32 FEV1 -matched female patients with COPD and 15 age-matched healthy women for 1 week using an accelerometer. In addition, we assessed lung function measurements, questionnaires for generic and respiratory health status (12-Item Short Form Survey, SF-12; St. George's Respiratory Questionnaire, SGRQ), dyspnoea (modified Medical Research Council dyspnoea scale, mMRC) and fatigue (Multidimensional Fatigue Inventory, MFI-20). Results: Patients with LAM (mean age 52.7 years, mean FEV1 62.7% predicted) showed reduced SPD, PAL and MMA (p<0.01) compared with healthy controls and reduced MMA (p=0.032) compared with female patients with COPD (mean age 65.2 years, mean FEV1 62.6% predicted). In multivariate regression analyses, adjusting for FEV1 and long-term oxygen therapy, either generic health status (SF-12 physical health) or fatigue (MFI-20) were the strongest independent predictors for SPD in patients with LAM (p=0.006 and p=0.004, respectively). Conclusions: Physical activity in daily life is substatially reduced in LAM, when compared with healthy controls and COPD - indicating a disease specific impact. The regular assessment of fatigue and generic health status may improve disease management in LAM by taking daily physical activity of patients with LAM more adequately into account.